2023
DOI: 10.1039/d3cp00779k
|View full text |Cite
|
Sign up to set email alerts
|

Single atom supported on MXenes for the alkaline hydrogen evolution reaction: species, coordination environment, and action mechanism

Abstract: The efficient alkaline hydrogen evolution reaction on RuS–Mo2Ti2C3O2 is achieved by the synergistic effect of Mo2Ti2C3O2 and atomic state Ru.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…From the above analysis, it is worth noting that the MXene–MOF hybrid with SACs immobilized on the surface exhibits enhanced HER performance compared with the bare MXene, representing its better hydrogen binding ability. 69…”
Section: Resultsmentioning
confidence: 99%
“…From the above analysis, it is worth noting that the MXene–MOF hybrid with SACs immobilized on the surface exhibits enhanced HER performance compared with the bare MXene, representing its better hydrogen binding ability. 69…”
Section: Resultsmentioning
confidence: 99%
“…S1 (ESI†). 15 Considering its advantages in alkaline HER, the 9 transition metal elements (Fe, Co, Ni, Ru, Rh, Pd, Os, Ir, and Pt) of the VIII group are introduced into Ru S –Mo 2 Ti 2 C 3 O 2 to replace the –O terminal group and explore the synergistic effect between the bimetallic atoms. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Our previous report confirmed that the anchoring of Ru SAs on a Mo-based MXene (Mo 2 Ti 2 C 3 O 2 ) could effectively improve the catalyst's ability for water splitting and eliminating water dissociation as the rate-limiting step. 15 However, the strong affinity of Ru for *OH results in a poisoning effect on the surface site, which hinders the desorption of *OH and the readsorption of *H 2 O, resulting in the desorption of *OH on Ru being the rate limiting step in the HER process. 16 Therefore, new strategies for the desorption or transfer of *OH on Ru sites are essential to further promote the Volmer step and improve the performance of alkaline HERs.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of individual TM atom in a near-atomic state also facilitates the formation of activation centers for the decomposition of H 2 O. 49…”
Section: Resultsmentioning
confidence: 99%